25 Years in a Nutshell IMIA-NI, 1982 2007 - Tallberg, M. (Yearbook of Medical Informatics, 2008)
Objective When invited to give an overview of nursing informatics I found it natural to celebrate the 25th anniversary of the International Medical Informatics Special Interests Group on Nursing Informatics (IMIA SIG NI) with a “mini history” from my own perspective.Method The method is historical. Sources are from the IMIA-NI web site, conference proceedings and programs, my private archive and reminiscences.Results and conclusions IMIA-NI has l “left its cradle” quite a while ago, and is now leading the nursing informatics world, thanks to its voluntary, enthusiastic and devoted leaders, WG chair persons, and national members. The newly reinforced executive also works hard to disseminate nursing informatics to the third world.
Keywords: Nursing informatics; nursing history; IMIA-NI; terminology